EFFECTIVE WHITEBOARD AS LEARNING MEDIA FOR HYBRID LEARNING SYSTEM IN HIGH SCHOOL - Alfina Mutiara Widyastuti; Alya Fauzia Zahra; Sintiya Erdiyana; Vika Haristianti (Universitas Pendidikan Indonesia, 2022)
At the beginning of 2020, COVID-19 was a virus that spread and occurred simultaneously in various countries around the world, including Indonesia. This pandemic has an impact on sectors in Indonesia, one of which is the impact on education. With this pandemic, the government has implemented online learning until finally the government has implemented hybrid learning. This study's purpose is to determine whether this hybrid learning is effective in grade 12 students. Data collection was carried out in distributing questionnaires, interviewing grade 12 students and making direct observations to several schools. The results of our analysis show that hybrid learning for grade 12 students is considered less effective because students experience several changes in learning outcomes, understanding of the material and lack of communication between teachers and friends. However, because this research is still early, we will use the results of this study as the basis for further research where we will discuss the tools or products that are assembled regarding user needs in solving problems that occur in hybrid learning. Keywords - Education, Hybrid, Pandemic, Student.